THE NEED OF LEARNING MEDIA ARTS IN JUNIOR HIGH SCHOOL (STUDY ON GRADE VII STUDENTS OF JUNIOR HIGH SCHOOL NEGERI 1 MOJOLABAN) - Kartika Mardikaningrum; Slamet Supriyadi; Sudiyanto Sudiyanto (Proceeding of International Conference on Art, Language, and Culture, 2017)
: In the learning of art and culture, media functioned as a means to achieve learning objectives. Role of instructional media is very important in the learning of art and culture, that is to improve student creativity. But in learning art and culture, the role of media is considered not important. This study aims to determine the needs of cultural and arts learning media in SMP N 1 Mojolaban especially class VII. The methodology of this research is survey research conducted to some students of class VII SMP N 1 Mojolaban. The results of this study that as many as  66,6 % require video-based media. The use of video media in the learning process can provide optimal results when used appropriately, in a sense in accordance with the subject matter that supports.